Development of KineMaster Application as ICT-Based Arabic Learning Media - Furoidah, Asni (Nurul Jadid University, 2024)
Developing effective Arabic language instruction in the digital era requires the integration of innovative media that are both accessible and pedagogically sound. This study explores the development and application of the KineMaster application as an ICT-based tool to support Arabic language learning in Islamic educational settings. The research is driven by the need to enhance student engagement, contextual understanding, and teacher creativity through multimedia learning materials. Using the ADDIE development model comprising Analysis, Design, Development, Implementation, and Evaluation, this study focused on the creation of animated video content tailored to Arabic learning themes. Data were collected through classroom observations and teacher reflections. The findings demonstrate that KineMaster enables teachers to produce visually engaging and thematically coherent materials that improve student motivation and comprehension. The application proved effective in both face-to-face and online learning contexts, offering a flexible and user-friendly platform for instructional innovation. This research suggests that KineMaster can serve as a practical alternative for developing creative and interactive Arabic learning media in line with 21st-century educational practices.